Equine dung as an organic nitrogen supplement in compost formulation for cultivation of white button mushroom [Agaricus bisporus J.E. Lange (Imbach)] - Roohi Jan; Sachin Gupta; Sudheer Kumar Annepu; Moni Gupta (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: The present study aimed to utilize the equine dung as an organic nitrogen supplement in commercial compost formulations for the cultivation of white button mushroom.